اندمال الكسور في ظروف الحقن الموضعي للصادات الحيوية عند مرضى ذات العظم والنقي المزمنة - جوني, أحمد (Latakia University Journal -Medical Sciences Series, 2018)
The study included (342) patients with chronic osteomyelitis of the fourth grade according to the classification of Mader. Most of the cases were followed by a war injuries (261) cases,( 53 ) cases of traffic accidents, (17) cases of work injuries , and (11) cases following hapitual injuries. The local injection of antibiotics method was used in the focal point of the infected fracture where the suitable antibiotic was selected according to the result of antibiogram . The cases were monitored for three months after the beginning of the local injection by conducting successive radiographs to monitor the formation of the callus. Callus formation was observed within a month and a half in (27) cases and within 3 months in( 231) cases and no radiologic signs of callus were observed in (84) cases. local injection of the antibiotics at the focal point of the infected fracture had given positive results in (258) cases (75.4% of the cases) and in (84) cases (24.6%) was ineffective. شملت الدراسة (342) مصاباً بذات العظم والنقي المزمنة من الدرجة الرابعة حسب تصنيف Mader . كانت معظم الحالات تالية لاصابة حربية (261) حالة وفي (53) حالةكان السببفيها حوادث سير و في (17) حالة كانت ذات العظم والنقي تالية لاصابات عمل و في (11) حالة تلت ذات العظم والنقي المزمنة رضوضاً اعتيادية. استخدمت طريقة الحقن الموضعي للصادات الحيوية في بؤرة الكسر المخموج حيث تم اختيار الصاد المناسب وفق نتيجة الزرع والتحسس الجرثومي و تمت مراقبة الحالات لمدة ثلاثة أشهر بعد بدء عملية الحقن و ذلك باجراء الصور الشعاعية المتعاقبة لمراقبة تشكل الدشبذ العظمي . لوحظ تشكل دشبذ عظمي خلال شهر ونصف في (27) حالة وخلال 3 أشهر في (231) حالة ولم تظهر أية علامات شعاعية لتشكل دشبذ عظمي في (84) حالة من الحالات . مكنت طريقة الحقن الموضعي للصادات في بؤرة الكسر المخموج من الحصول على نتائج ايجابية في (258 حالة – 75.4% من الحالات) و في (84 حالة – 24.6% من الحالات) لم تكن فعالة .